1994
DOI: 10.1042/cs0870697
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fasting on Fatty Acid Kinetics and on the Cardiovascular, Thermogenic and Metabolic Responses to the Glucose Clamp

Abstract: 1. The effects of fasting for 12, 36 and 72 h were examined in 19 normal subjects. Each subject was studied before and during a euglycaemic (4 mmol/l) hyperinsulinaemic (100 m-units min-1 m-2) clamp. Measurements were made of palmitate turnover and oxidation, glucose disposal, thermogenesis, intermediary metabolites and cardiovascular variables. 2. Basal respiratory exchange ratio fell from 0.78 +/- 0.01 to 0.75 +/- 0.01 to 0.72 +/- 0.01 with fasting (P < 0.001). In response to the clamp it rose to 0.91 +/- 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
27
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 0 publications
5
27
0
Order By: Relevance
“…Starvation has consistently been shown to decrease IS and deteriorate postprandial glucose tolerance. 7,8,17 Similarly, further studies have demonstrated a decline in clamp-derived IS within 24 h (200 kcal per day) and 5 days (À50% energy) of CR, respectively. 10,11 Severe carbohydrate restriction induces postprandial hyperglycemia and IR at skeletal muscle to shift fuel to the brain.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Starvation has consistently been shown to decrease IS and deteriorate postprandial glucose tolerance. 7,8,17 Similarly, further studies have demonstrated a decline in clamp-derived IS within 24 h (200 kcal per day) and 5 days (À50% energy) of CR, respectively. 10,11 Severe carbohydrate restriction induces postprandial hyperglycemia and IR at skeletal muscle to shift fuel to the brain.…”
Section: Discussionmentioning
confidence: 90%
“…Fasting (1 --3 days) consistently caused a decline in IS assessed by clamp-and intravenous glucose tolerance test. 7,8,17 Studies with less severe CR, however, provided rather inconsistent results. Although some studies have found an impairment of IS within 1 --5 days of CR (p50% energy) in healthy lean subjects, 10,11 clamp-derived IS has been shown to be sustained following 7 days of CR at an energy intake of 60 kJ kg À1 body weight per day.…”
Section: Introductionmentioning
confidence: 99%
“…Although we did not compare glucose sensitivity before and after the fast, it is known that fasting inhibits insulin-mediated whole body oxidative glucose disposal (25,47), presumably via operation of the glucose-fatty acid cycle (32). However, when FFAs are available in excess after lipid-heparin infusion, glucose 6-phosphate levels fall below control levels, suggesting inhibition of glucose transport/phosphorylation rather than via elevation of acetyl-CoA/CoA and NADH/ NAD ϩ (34).…”
Section: Discussionmentioning
confidence: 93%
“…Three to four days of fasting results in elevated plasma FFA concentration (15, 47) and impaired glucose uptake (25,47). However, the glucose-"sparing" effect in this condition is understood to be mediated by the increase in circulating ketones, whose metabolism inhibits hexokinase via operation of the glucose-fatty acid cycle (32).…”
mentioning
confidence: 99%
“…The availability of the glucose clamp technique in combination with indirect calorimetry to assess CHO oxidation has allowed this to be studied in more detail. It is now clear that the insulin resistance produced by acute starvation (up to 72 h) is entirely due to a decrease in the ability of insulin to stimulate CHO oxidation (Mansell & Macdonald, 1990;Webber et al, 1994). In healthy subjects who starve for up to 72 h, insulin stimulated glucose disposal is reduced by up to 50%.…”
Section: Dietary Cho and Glucose Tolerancementioning
confidence: 99%